Management of a Class I malocclusion with traumatically avulsed maxillary central and lateral incisors - Mostafa, Nesrine Z. (Angle Orthod, 2018)
This case report describes orthodontic space closure for managing an avulsed maxillary central incisor and a lateral incisor in a growing girl with a Class I deep bite malocclusion with moderate lower and mild upper crowding. The treatment approach moved a central incisor across the midline and substituted a lateral incisor for a central incisor, in combination with canine substitution. Veneers on all maxillary anterior teeth attained acceptable esthetics. The right central incisor was moved to serve as the avulsed left central incisor. The right lateral incisor was moved to the position of the right central incisor and restored. The canines on both sides were substituted as lateral incisors; the posterior occlusion was left in Class II. Mesialization of central and lateral incisors with prosthetic rehabilitation is an acceptable treatment option.